Drooling in Patients with Cerebral Palsy: The Effectiveness of Botulinum Toxin A Treatment - O. A. Klochkova; A. L. Kurenkov; H. M. Karimova; B. I. Bursagova; L. S. Namazova-Baranova; L. M. Kuzenkova; A. M. Mamedyarov; G. M. Dvoryakovskaya (Union of pediatricians of Russia, 2015)
Background. Drooling (sialorrhea) is a complex medical and social problem of patients with cerebral palsy (CP). During the last decade many methods for drooling correction in CP are under active development.Aim: to evaluate the effectiveness and safety of the first and repeated injections of botulinum toxin A (BTA) for correcting drooling in children with CP.Methods. 13 children (2 years - 14 years 7 months) with spastic forms of CP and drooling resistant to non-drug treatment. Drooling was evaluated with the Drooling Impact Scale - DIS before, 1, 3 and 6 months after the BTA injections. Parotid and submandibular salivary glands were injected under ultrasound control with Dysport - 1 group (5 children) or Botox - 2 group (8 children). The total dose of Dysport for the all glands was 120-320 U (3,8-14,5 U/kg), Botox - 30-100 U (2,5-4,5 U/kg). The median of the basic DIS index was 77 (64-90) points in the first group and 58 (53-66) points in the second group.Results. One month after the BTA injections the DIS index decreased by 20 and more points in 6 (42,2%) patients, by 10-19 points in 7 (53,8%) children. There were no persistent side effects and no difference in the BTA effectiveness between the two groups. The mean decrease of DIS was 30% in both groups. 3 months after the injections 2 patients (15,4%) kept 20 points decrease of the DIS index, 6 patients (46,2%) demonstrated 10 points decrease. 6 months after injections nearly all patients returned to the basic level of drooling. Repeated injections of the BTA demonstrated the same tendency and duration of the DIS changes. There was no significant correlation between the GMFCS level and the drooling intensity.Conclusion. BTA injections into salivary glands of children with CP was an effective and safe method of drooling correction with the maximum effect taking place 2-4 weeks after the injections and a stable effect - 3 months after the injections.